Screening of chilli pepper (Capsicum spp.) lines for resistance to the begomoviruses causing chilli leaf curl disease in India. (October 2017) - Srivastava, Arpita; Mangal, Manisha; Saritha, R.K.; Kalia, Pritam
Abstract: Resistance breeding program relies on identification of stable resistant sources. It starts with first identifying lines free from disease when screened under field followed by their screening by challenge inoculation for further confirmation of their resistance behavior. Following this approach, in the present study 60 germplasm lines of Capsicum annuum L., one each of C. baccatum, C. chinense, C. chacoense and two of C. frutescens and were assessed for resistance to leaf curl disease under field screening. As screening was carried out under natural disease conditions, chances of escape cannot be rule out. To ascertain the response of the identified chilli lines for resistance to leaf curl disease, the experiment was undertaken including the identified resistant lines for three more consecutive seasons with susceptible lines namely Pusa Jwala as infector rows at regular intervals to confirm their resistance response. At the end of first season of screening, sixteen lines were isolated (all of C. annuum species) showing mild or no disease symptoms in comparison to other lines under test. The screening process was continued for three seasons and the lines found resistant at the end of one season were screened in the next season also, while the susceptible lines were excluded from the study. At the end of four seasons of screening trial, three lines namely DLS-Sel-10, WBC-Sel-5 and PBC-142 showed resistance against leaf curl disease. Highlights: 65 genotypes of chilli pepper were assessed for resistance to leaf curl disease under field screening for four consecutive seasons. At the end of four seasons of screening, three lines namely DLS-Sel-10, WBC-Sel-5 and PBC-142 were found resistant. Dendrogram constructed from SSR profiling of 24 genotypes out of these 65 lines, clustered resistant genotypes together in one group.